2020
DOI: 10.1103/physreva.101.012313
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-assisted probabilistic coherence distillation for mixed states

Abstract: The remarkable phenomenon of catalyst tells us that adding a catalyst could help state transformation. In this paper, we consider the problem of catalyst-assisted probabilistic coherence distillation for mixed states under strictly incoherent operations. To this end, we first present the necessary and sufficient conditions for distilling a target pure coherent state from an initial mixed state via stochastic strictly incoherent operations and the maximal probability of obtaining the target pure state from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…These results tell us that when we want to deterministically transform a pure state into another one, IO and SIO have the same set of accessible pure states. After that, the probabilistic transformation between pure coherent states under SIO was studied in [20,21]. The results of [17,22,23] showed that the set of accessible states through IO and SIO are still the same when qubit states are deterministically transformed.…”
Section: Introductionmentioning
confidence: 99%
“…These results tell us that when we want to deterministically transform a pure state into another one, IO and SIO have the same set of accessible pure states. After that, the probabilistic transformation between pure coherent states under SIO was studied in [20,21]. The results of [17,22,23] showed that the set of accessible states through IO and SIO are still the same when qubit states are deterministically transformed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this theory, many other coherence measures were also proposed, see [8,10] for a detailed review of them. Recently, coherence was analyzed in a number of contexts, for example, its distillation and dilution [11][12][13][14][15][16], its basis dependency [17][18][19], its role in interpreting the wave-particle duality [20,21], and its applications in certain practical tasks [22][23][24][25][26][27][28]. Besides, there are also evidences that the coherence provides an indicator of quantum phase transitions in spin systems [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a critical issue is to investigate coherence manipulations via free operations. Many protocols of coherence manipulation have been proposed based on various physical scenarios [16,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], and some have been demonstrated in the experiment [59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%